Reaction of upland rice genotypes to the brown spot disease pathogen Bipolaris oryzae - Mwendo, M. M.; Ochwo-Ssemakula, M.; Lamo, J.; Gibson, P.; Edema, R. (African Journal of Rural Development (AFJRD), 2017)
Low yields in rice (Oryza sativa L.) are attributed to several factors but diseases represent one of the main constraints. The Brown spot disease (caused by Bipolaris oryzae (Breda de Haan) Shoem) in most cases causes considerable losses in rice growing areas. These yield loses could be averted through development and deployment of resistant varieties. In this study, a field experiment was conducted at the National Crops Resources Research Institute (NaCRRI) – Namulonge, Uganda during 2013 with the objective of identifying new sources of resistance to brown spot disease. Among the 100 tested rice lines, 18 lines were rated as highly resistant, 52 resistant, 27 moderately resistant and three lines including the checks were susceptible. The results revealed that there was significant variation in brown spot resistance among the genotypes tested. The identified resistant lines will be utilized in rice breeding program in Uganda for development of brown spot resistant genotypes.
Keywords: Brown spot; Bipolaris oryzae; Oryza sativa; Sources of resistance; Uganda